The Perceived Corporate Social Responsibility of Major Sport Organizations by the German Public: An Empirical Analysis During the COVID-19 Pandemic - Thormann, Tim F.; Wicker, Pamela (Frontiers in Sports and Active Living, 2021)
Sport governing bodies have played a special role in society during the first wave of the Covid-19 pandemic. Following stakeholder theory and consumption capital theory, this study investigated the actions of the German Bundesliga (DFL), Union of European Football Associations (UEFA), and the International Olympic Committee (IOC) during this phase, as perceived by the German population, through the lens of corporate social responsibility (CSR). Based on a representative sample of the German resident population (N=1000), the study examined individual characteristics that influenced the perceived CSR of these organizations and what population clusters emerge from this perception. The survey applied a CSR scale that was previously validated in a professional team sports context. The results confirmed the equally strong applicability of the scale to the sport governing context. Cluster analysis yielded three distinctive clusters, namely “Supporters”, “Neutral observers”, and “Critics”. Regression analyses and cluster analysis identified those with frequent consumption and high involvement as rating the actions of the three sport organizations more positively and are stronger represented in the “Supporters” cluster. In contrast, those threatened the most by the virus are overrepresented in the “Critics” cluster.